2022
DOI: 10.3389/fmars.2022.921451
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Filtration: An Untapped Ecosystem Service

Abstract: Marine pathogens present serious challenges to aquaculture, fisheries productivity, and marine conservation requiring novel solutions to identify, control, and mitigate their effects. Several ecological habitats, such as mangroves and wetlands can recycle waste and serve as aquatic filtration systems. While nutrient cycling and other ecosystem services of these habitats have been well-studied, their potential to remove pathogens and mechanisms of filtration remain largely unstudied. Here, we review how mangrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Given the decrease in the removal of putative bacterial pathogen potential in fragmented seagrass meadows, it could be argued that seagrass decline would lead to coastal-living humans and marine organisms suffering from high-risk diseases. Therefore, we suggest the recovery and protection of the declining seagrass meadows worldwide, which have important implications for human and marine organism health protection (Klohmann and Padilla-Gamiño, 2022).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Given the decrease in the removal of putative bacterial pathogen potential in fragmented seagrass meadows, it could be argued that seagrass decline would lead to coastal-living humans and marine organisms suffering from high-risk diseases. Therefore, we suggest the recovery and protection of the declining seagrass meadows worldwide, which have important implications for human and marine organism health protection (Klohmann and Padilla-Gamiño, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…At a global scale, more than 80% of domestic wastewater is discharged into rivers or ocean without any treatment (Programme, U.N.W.W.A 2017), thus introducing bacterial pathogens of human and marine organisms to coastal waters (Stewart et al, 2008;Perkins et al, 2014). Coastal-living humans can suffer diseases and other health-related effects when exposed to bacterial pathogens in the ocean (Graciaa et al, 2018;Klohmann and Padilla-Gamiño, 2022). Seagrass meadows, mainly distributed along the coastal areas, are recently highlighted for reducing seawater bacterial pathogens capable of causing diseases in humans and marine organisms (Lamb et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desalination of seawater, brackish water, or industrial wastewater is an effective strategy to address this crisis and has drawn considerable attention . Currently, mature water desalination technologies such as the reverse osmosis process, , thermal distillation, , and chemical filtration , have been used to produce fresh water mostly in the economically developed coastal areas. Traditional desalination is something of a controversial technology.…”
Section: Introductionmentioning
confidence: 99%
“…In general, studies have shown that a multitude of non-host species can consume or obstruct infective stages of a large range of parasite groups from different environments (Thieltges et al 2008 ; Johnson and Thieltges 2010 ; Johnson et al 2010 ). Especially in aquatic environments, where vectors are much less common than on land and where transmission of parasites and pathogens mainly occurs via the water column, ‘pathogen filtration’ by non-hosts in form of physical obstructions by vegetation or filter feeding removal by bivalve beds has received increased interest as a potential ecosystem service and disease managing approach (Burge et al 2016 ; Lamb et al 2017 ; Klohmann and Padilla-Gamiño 2022 ). However, non-host species differ in their capability to consume or obstruct infective stages depending on the specific parasites or pathogens in question and some non-host species may not show an effect at all (e.g., Hopper et al 2008 ; Orlofske et al 2015 ; Welsh et al 2014 , 2020 ; Koprivnikar et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%